Application Of The Peer Tutor Method In Assisting The Mathematics Learning Process Of Deaf Students - Anditiasari, Nungki; Waluya, St Budi; Dewi, Nuriana Rachmani (Universitas Wiralodra, 2023)
This study aims to determine the application of the peer tutor method to the mathematics learning process of 5 deaf students in class X SMALB Negeri Slawi. The method used is the descriptive method. The data collection is done by testing, observation, and documentation. Data analysis was carried out by data reduction, presentation, and conclusion, which is the model of Miles and Huberman. Based on the results of data analysis, it can be concluded that peer tutors provide convenience for deaf students with below-average abilities in working on math problems. This is because deaf students get direction and assistance from deaf students who already understand and act as tutors so they can solve math problems. The application of the peer tutor method facilitates the learning process of deaf students. Students communicate with each other to assist, increase learning activity, and solve problems together it can affect the completeness of the learning outcomes of deaf students. In the learning process, peer tutors can be used as an alternatively appropriate and effective learning method, especially for deaf students.